Historical Analysis of the Format of Guarantee in the Literature of Shiite Jurisprudence and Law - Sayyed Ali Jabbar Golbaghi Masuleh (آموزه‌‌های فقه مدني, 2020)
In the literature of Shiite jurisprudence, the formology of legal jurisprudence is one of the general rules of transactions. Sometimes, Shiite jurists disagree about the format of some legal jurisprudential practices. Guarantee is one of the acts whose formology is a point of contention. Well-known Shiite jurists consider guarantee to be a contract, while other jurists consider it to be a unilateral contract. An examination of the texts of Shiite jurisprudence shows that the followers of each of the two mentioned views, regardless of the historical course, which is one of the effective matters in recognizing rational credentials, turn to the interpretation of the format of guarantee. Therefore, the historical analysis of guarantee formology in the scope of Shiite jurisprudence literature is the aim of the present study, which descriptively examines the written works of Shiite jurisprudential doctrines and schools and assesses the possibility of speech from a new perspective and it comes to the conclusion that contrary to the two views mentioned above, guarantee has both forms of contract and unilateral at the same time, and the determination of each of these two forms depends on the will and action of those who undertake to write the guarantee and depending on their will, they can sometimes make a guarantee in the form of a contract and other times in the form of a unilateral.